A revision of the Mexican and Central American species of Vanilla plumier ex miller with a characterization of their its region of the nuclear ribosomal DNA - Soto Arenas, Miguel A.; Dressler, Robert L. (Lankesteriana: International Journal on Orchidology, 2013)
We present a revision of the Mexican and Central American species of Vanilla. There are 15 different species in the area; Vanilla costaricensis, V. cribbiana, V. dressleri, V. martinezii and V. sarapiquensis are here proposed as new taxa, and V. pompona subsp. pittieri and V. pompona subsp. grandiflora are recognized at subspecific rank. Vanilla calyculata, V. hartii, V. helleri, V. inodora, V. insignis, V. odorata, V. phaeantha, V. planifolia, V. pompona and V. trigonocarpa are also described, illustrated, and their nomenclature, typification, distribution, and other aspects of interest are discussed. Additionally, we include a key to the species. Several Mexican and Central American species of Vanilla are closely related to V. planifolia, V. x tahitensis, and V. pompona, the cultivated species of the genus, and these are thus important in plant breeding. We also include a cladistic analysis of nucleotidic sequences of the internal transcribed spacer region of the nuclear ribosomal DNA, showing that this popular molecular marker is of sufficient variation to allow for species discrimination, permitting, with some exceptions that are discussed, the recognition of sterile samples and indicating that it is a good molecular marker to infer the phylogeny of this group. The similarity and relationship between V. x tahitensis* and V. odorata is discussed.